2013
DOI: 10.5653/cerm.2013.40.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of norepinephrine transporter and norepinephrine in human placenta cause pre-eclampsia through regulated trophoblast invasion

Abstract: ObjectiveWe investigated the norepinephrine transporter (NET) expression in normal and pre-eclamptic placentas and analyzed the invasion activity of trophoblastic cells based on norepinephrine (NE)-NET regulation.MethodsNET and NE expression levels were examined by western blot and enzyme-linked immunosorbent assay, respectively. Trophoblast invasion activity, depending on NE-NET regulation, was determined by NET-small interfering RNA (siRNA) and NET transfection into the human extravillous trophoblast cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A study conducted by Na et al reported a reduced NET mRNA expression in preeclamptic placentas compared with normal placentas. More interestingly, they also observed that maternal plasma NE concentration was increased in preeclamptic women compared to normal pregnant women [77]. Similar findings were observed by Lampinen et al, who also noted an increase in plasma levels of norepinephrine in women with a previous history of PE [78].…”
Section: The Role Of Monoamine Oxidase (Mao) In the Pathophysiologsupporting
confidence: 64%
“…A study conducted by Na et al reported a reduced NET mRNA expression in preeclamptic placentas compared with normal placentas. More interestingly, they also observed that maternal plasma NE concentration was increased in preeclamptic women compared to normal pregnant women [77]. Similar findings were observed by Lampinen et al, who also noted an increase in plasma levels of norepinephrine in women with a previous history of PE [78].…”
Section: The Role Of Monoamine Oxidase (Mao) In the Pathophysiologsupporting
confidence: 64%
“…However, before this study, the feasibility of norepinephrine had not been explored for women with preeclampsia with uteroplacental insufficiency. Na et al [22] compared maternal norepinephrine in pregnant women with preeclampsia and normotensive pregnant women and found that parturients with preeclampsia had prominently increased levels of norepinephrine, raising the concern regarding whether women with preeclampsia would remain sensitive to exogenous norepinephrine. In this study, intermittent boluses were applied rather than the continuous infusion of norepinephrine or ephedrine to rescue spinal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…This finding raised questions about whether these women would still be sensitive to exogenous norepinephrine. 17 According to a study by Minzter et al in 2010, Norepinephrine had no impact on the fetal arterial perfusion pressure, and the fetoplacental microcirculation was unaffected. 18 In a study, Left Uterine Displacement (LUD) was not given post-administration of spinal anesthesia.…”
Section: Discussionmentioning
confidence: 98%